The Association Between Provider Price and Complication Rates for Outpatient Surgical Services - Whaley, Christopher (J Gen Intern Med, 2018)
BACKGROUND: Wide variations exist in price and quality for health-care services, but the link between price and quality remains uncertain. OBJECTIVE: This paper used claims data from a large commercially insured population to assess the association between both procedure- and provider-level prices and complication rates for three common outpatient surgical services. DESIGN: This is a retrospective cohort study. SETTING: The study used medical claims data from commercial health plans between 2009 and 2013 for three outpatient surgical services—joint arthroscopy, cataract surgery, and colonoscopy. MAIN MEASURES: For each procedure, price was assessed as the sum of patient, employer, and insurer spending. Complications were identified using existing algorithms specific to each service. Multivariate regressions were used to risk-adjust prices and complication rates. Provider-level price and complication rates were compared by calculating standardized differences that compared provider risk-adjusted price and complication rates with other providers within the same geographic market. The association between provider-level risk-adjusted price and complication rates was estimated using a linear regression. KEY RESULTS: Across the three services, there was an inverse association between both procedure- and provider-level prices and complication rates. For joint arthroscopy, cataract surgery, and colonoscopy, a one standard deviation increase in procedure-level price was associated with 1.06 (95% CI 1.05–1.08), 1.14 (95% CI 1.11–1.16), and 1.07 (95% CI 1.06–1.07) odds increases in the rate of procedural complications, respectively. A one standard deviation increase in risk-adjusted provider price was associated with 0.09 (95% CI 0.07 to 0.11), 0.02 (95% CI 0.003 to 0.05), and 0.32 (95% CI 0.29 to 0.34) standard deviation increases in the rate of provider risk-adjusted complication rates, respectively. LIMITATIONS: Results may be due to unobserved factors. Only three surgical services were examined, and the results may not generalize to other services and procedures. Quality measurements did not include patient satisfaction or experience measures. CONCLUSIONS: For three common outpatient surgical services, procedure- and provider-level prices are associated with modest increased rates of complication rates. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-018-4506-7) contains supplementary material, which is available to authorized users.